2015
DOI: 10.3389/fnbeh.2015.00213
|View full text |Cite
|
Sign up to set email alerts
|

Prepulse inhibition predicts spatial working memory performance in the inbred Roman high- and low-avoidance rats and in genetically heterogeneous NIH-HS rats: relevance for studying pre-attentive and cognitive anomalies in schizophrenia

Abstract: Animal models of schizophrenia-relevant symptoms are increasingly important for progress in our understanding of the neurobiological basis of the disorder and for discovering novel and more specific treatments. Prepulse inhibition (PPI) and working memory, which are impaired in schizophrenic patients, are among the symptoms/processes modeled in those animal analogs. We have evaluated whether a genetically-selected rat model, the Roman high-avoidance inbred strain (RHA-I), displays PPI deficits as compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 80 publications
3
33
0
Order By: Relevance
“…Remarkably, a general finding of all PPI experiments was that the total averaged %PPI was consistently lower in RHA-I than in RLA-I rats, which is in agreement with previous studies showing that the RHA-I strain displays a relative deficit in PPI (Oliveras et al 2015; Esnal et al 2016; Del Río et al 2014). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Remarkably, a general finding of all PPI experiments was that the total averaged %PPI was consistently lower in RHA-I than in RLA-I rats, which is in agreement with previous studies showing that the RHA-I strain displays a relative deficit in PPI (Oliveras et al 2015; Esnal et al 2016; Del Río et al 2014). …”
Section: Discussionsupporting
confidence: 91%
“…We have recently proposed that one such model, the Roman rat strains, displays genetically determined deficits/impairments in several schizophrenia-related features (Del Rio et al 2014; Oliveras et al 2015; Esnal et al 2016). The Roman high- (RHA) and low-avoidance (RLA) rat lines/strains ( lines refers to the outbred, and strains refers to the inbred animals) have been selectively and bidirectionally bred for their rapid (RHA) vs extremely poor (RLA) ability to acquire the two-way active avoidance task (Bignami 1965; Driscoll and Battig 1982; Steimer and Driscoll 2003; Escorihuela et al 1999, Rio-Alamos et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with that, recent studies in rat-based model of schizophrenia-relevant symptom have shown that PPI is a positive predictor of spatial working memory and latent inhibition [33, 34]. Furthermore, previous studies have also shown dysfunctions in selective spatial attention in schizophrenia [35].…”
Section: Introductionmentioning
confidence: 58%
“…PPI expression is regulated by a wide corticolimbic and brainstem network, upon which prefrontal cortex (PFC) exerts an important neuromodulatory role (17)(18)(19)(20)(21). Although sensorimotor gating is not a cognitive process per se, it correlates well with several cognitive domains, such as executive function (22), WM (23)(24)(25), and social cognition (26) and likely shares neural substrates with these domains. We have previously shown that Df(16)A +/− mice exhibit a robust PPI deficit (12).…”
Section: Restoration Of Mirta22 Levels Prevents Deficits In Ppi Wm-dmentioning
confidence: 99%